Comparaison du potentiel insecticide des huiles essentielles de Ocimum gratissimum L. et de Ocimum canum Sims sur Pectinophora gossypiella Saunders (Lepidoptera : Gelechiidae), insecte ravageur du cotonnier en CÃ´te dâ€™Ivoire - Kobenan, Koffi Christophe; Tia, Vama Etienne; Ochou, Germain Elisabeth Cynthia; Kouakou, Malanno; Bini, Kouadio Kra Norbert; Dagnogo, Mamadou; Dick, Acka Emmanuel; Ochou, Ochou Germain (European Scientific Journal, ESJ, 2018)
The abusive use of synthetic pesticides in the phytosanitary protection of cotton in CÃ´te d’Ivoire threatens the viability of the production system. The search for alternative control methods is therefore necessary. Phytosanitary strategies involving plant-based biopesticides have been explored. The insecticidal activity of essential oils of plant species of the genus Ocimum has been the subject of numerous investigations. The objective of this study is to compare the insecticidal potential of two species of the same genus Ocimum gratissimum and O. canum on a major cotton pest, the pink worm Pectinophora gossypiella. Adults of the insect were exposed in the laboratory to the toxic effect of different concentrations of these oils by topical application using a micro applicator. The lethal concentrations causing respectively 50 % (LC50) and 90% (LC90) death in the populations tested were determined for each of the essential oils. The oil extracted from O. gratissimum was the most toxic with LC50 and LC90 respective values of 1.01 % and 5.05 % as compared to O. canum (LC50 = 11.33 % and LC90= 30.04 %). The high toxicity of O. gratissimum may be explained by the presence of 24.57 % thymol and 37.79 % p-cimene in its chemical composition. The extract of O. gratissimum has shown in laboratory the highest potentiel insecticidal activity, itâ€˜s field use can therefore be suggested for the control of this cotton pest.